A systematic literature review and narrative synthesis on the risks of medical discharge letters for patients' safety - Christine Maria Schwarz; Magdalena Hoffmann; Petra Schwarz; Lars-Peter Kamolz; Gernot Brunner; Gerald Sendlhofer (BMC, 2019)
Abstract Background The medical discharge letter is an important communication tool between hospitals and other healthcare providers. Despite its high status, it often does not meet the desired requirements in everyday clinical practice. Occurring risks create barriers for patients and doctors. This present review summarizes risks of the medical discharge letter. Methods The research question was answered with a systematic literature research and results were summarized narratively. A literature search in the databases PubMed and Cochrane Library for Studies between January 2008 and May 2018 was performed. Two authors reviewed the full texts of potentially relevant studies to determine eligibility for inclusion. Literature on possible risks associated with the medical discharge letter was discussed. Results In total, 29 studies were included in this review. The major identified risk factors are the delayed sending of the discharge letter to doctors for further treatments, unintelligible (not patient-centered) medical discharge letters, low quality of the discharge letter, and lack of information as well as absence of training in writing medical discharge letters during medical education. Conclusions Multiple risks factors are associated with the medical discharge letter. There is a need for further research to improve the quality of the medical discharge letter to minimize risks and increase patients' safety.